Lewy Body Disease Primate Model with α‐Synuclein Propagation from the Olfactory Bulb. Issue 10 (21st August 2022) - Sawamura, Masanori; Onoe, Hirotaka; Tsukada, Hideo; Isa, Kaoru; Yamakado, Hodaka; Okuda, Shinya; Ikuno, Masashi; Hatanaka, Yusuke; Murayama, Shigeo; Uemura, Norihito; Isa, Tadashi; Takahashi, Ryosuke
ABSTRACT: Background: Lewy body diseases (LBDs), which are pathologically defined as the presence of intraneuronal α‐synuclein (α‐Syn) inclusions called Lewy bodies, encompass Parkinson's disease, Parkinson's disease with dementia, and dementia with Lewy bodies. Autopsy studies have shown that the olfactory bulb (OB) is one of the regions where Lewy pathology develops and initiates its spread in the brain. Objective: This study aims to clarify how Lewy pathology spreads from the OB and affects brain functions using nonhuman primates. Methods: We inoculated α‐Syn preformed fibrils into the unilateral OBs of common marmosets ( Callithrix jacchus ) and performed pathological analyses, manganese‐enhanced magnetic resonance imaging, and 18 F‐fluoro‐2‐deoxy‐d ‐glucose positron emission tomography up to 6 months postinoculation. Results: Severe α‐Syn pathology was observed within the olfactory pathway and limbic system, while mild α‐Syn pathology was seen in a wide range of brain regions, including the substantia nigra pars compacta, locus coeruleus, and even dorsal motor nucleus of the vagus nerve. The brain imaging analyses showed reduction in volume of the OB and progressive glucose hypometabolism in widespread brain regions, including the occipital lobe, and extended beyond the pathologically affected regions. Conclusions: We generated a novel nonhuman primate LBD model with α‐Syn propagation from the OB. This model suggests that α‐Syn propagation from the OB is related to OB atrophy and cerebral glucose hypometabolism in LBDs. © 2022 International Parkinson and Movement Disorder Society.